Investment, Saving and the Inflationary Gap: Some Comments on Dr. Hansen's Models - Zawadzki, K. K. F. (Review of Economic Studies, 1953)
Journal Article Investment, Saving and the Inflationary Gap: Some Comments on Dr. Hansen's Models Get access K. K. F. Zawadzki K. K. F. Zawadzki London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 21, Issue 1, 1953, Pages 63–73, https://doi.org/10.2307/2296260 Published: 01 January 1953